A magnetic wave absorbing material with excellent wave absorbing performance in S band and a preparation method thereof

By designing the magnetic wave absorbing material of LaFe4Mn8 alloy, the problem of poor absorption performance in the S-band is solved in the existing technology, and excellent absorption performance and frequency bandwidth in the range of 2-8GHz is achieved. It is suitable for microwave radiation protection and stealth technology , and the preparation process is convenient and the cost is low.

CN114937872BActive Publication Date: 2024-12-17ANHUI JIHUA NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210353521.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-06
Publication Date
2024-12-17
Estimated Expiration
2042-04-06

AI Technical Summary

Technical Problem

The existing absorbing materials have poor absorption performance in the S (2-4GHz) band and the C (4-8GHz) band, especially in the S band, which is difficult to meet the needs of microwave radiation protection and stealth technology.

Method used

The LaFe4Mn8 alloy magnetic wave absorbing material was designed and prepared through the steps of batching, smelting, ball milling, molding, sintering and grinding to form the LaFe4-x-yGexVyMn8-Z-RZnzSnR alloy magnetic wave absorbing material, which has excellent S-band wave absorbing performance.

Benefits of technology

In the frequency range of 2-8GHz, especially in the S-band, the material exhibits excellent microwave absorption effect and wide bandwidth, and the preparation process is simple and low cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114937872B_ABST
    Figure CN114937872B_ABST
Patent Text Reader

Abstract

The present invention provides a magnetic absorbing material with excellent absorbing performance in the S band and a preparation method thereof, and relates to the technical field of magnetic absorbing material processing. The magnetic absorbing material with excellent absorbing performance in the S band is a LaFe4Mn8 alloy magnetic absorbing material, and its preparation method mainly includes the steps of batching, smelting, ball milling, molding, sintering, grinding, etc. The present invention overcomes the shortcomings of the prior art, and by designing an alloy magnetic absorbing material, it has excellent absorbing performance within 2-8GHz, especially in the S band, and the preparation process is easy to master, the production cost is low, and it is easy to promote production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic wave-absorbing material processing, and in particular to a magnetic wave-absorbing material with excellent wave-absorbing performance in the S band and a preparation method thereof. Background Art

[0002] In recent years, with the widespread application of various electronic products, microwave radiation has become a new source of pollution, posing a serious threat to human health. For this reason, people have developed various absorbing materials to protect against microwave radiation. At the same time, the development of military stealth technology has promoted the development of absorbing materials.

[0003] Traditional absorbing materials mainly include ferrite and magnetic metal (alloy) powders. Although ferrite is the most widely used and effective anti-electromagnetic interference material, its application is greatly limited due to its low saturation magnetization, poor thermal stability and corrosion resistance. Magnetic metal powders have high Curie temperature, good thermal stability, good saturation magnetization and particle shape effect, high complex magnetic permeability and low eddy current loss, and small matching thickness (millimeter level), so they have good application prospects as electromagnetic wave absorbers.

[0004] Currently, the most widely used soft magnetic alloy powders are mainly Fe, Co, Ni and their alloy powders, etc., and because rare earth elements have an unfilled 4f electron layer, and the fourth layer of electrons can be well shielded by the fifth layer of electron shell, the 4f electron layer is less affected by the potential field of other neighboring ions. The special structure of rare earth metals gives them unique electromagnetic specificity that many other elements do not have, which can improve the microwave absorption performance of the alloy.

[0005] Although certain research progress has been made in alloy absorbing materials, the research on the absorbing performance in the S (2-4GHz) band and the C (4-8GHz) band, especially in the S band, is still not ideal; therefore, it is of great significance to develop an absorbing material with good absorbing performance in the 2-8GHz range, especially in the S band. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a magnetic absorbing material with excellent absorbing performance in the S band and a preparation method thereof. By designing a LaFe4Mn8 alloy magnetic absorbing material, this material has excellent absorbing performance in the 2-8GHz range, especially in the S band, and the preparation process is easy to master, the production cost is low, and it is easy to promote production.

[0007] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:

[0008] A magnetic wave absorbing material with excellent wave absorbing performance in the S band, characterized in that the magnetic wave absorbing material is a LaFe4Mn8 alloy magnetic wave absorbing material, and the alloy magnetic wave absorbing material is composed of LaFe in terms of atomic ratio 4-x- y Ge x V y Mn 8-Z-R Zn z Sn R .

[0009] The preparation method of the magnetic wave absorbing material with excellent wave absorbing performance in the S band comprises the steps of batching, smelting, ball milling, molding, sintering, grinding and the like.

[0010] Preferably, the batching step is: using metal La, Fe, Ge, V, Mn, Zn, Sn with a metal purity greater than 99.0% as raw materials, according to LaFe 4-x-y Ge x V y Mn 8-Z-R Zn z Sn R (0.2 ≤x≤0.6; 0.1≤y≤0.5; 0.1≤z≤0.5; 0.1≤R≤0.7) atomic ratio ingredients;

[0011] Preferably, the smelting step comprises: smelting in a standard vacuum melting furnace under argon protection, and casting to obtain an alloy ingot;

[0012] Preferably, the ball milling step comprises: crushing the obtained alloy ingot into coarse powder with a particle size of less than 0.5 mm, and then sieving it under a 40-mesh sieve to obtain alloy coarse powder; placing the crushed alloy coarse powder and zirconia balls in a zirconia tank at a mass ratio of 15:1, and ball milling for 5-12 hours under the protection of anhydrous ethanol, with a ball mill speed of 200-300 r / min;

[0013] Preferably, the sintering molding step is: taking out the ball-milled powder from a nitrogen-protected glove box, drying it, and then pressing it into a blank with a diameter of 20 mm and a height of 10 mm;

[0014] Preferably, the sintering step is: placing the blank into a vacuum magnetic field microwave sintering furnace for high temperature sintering, the sintering temperature is 800-1000°C, the temperature is kept for 20-40min, the microwave frequency is 1.0-3.5kW, and the magnetic field is 1.0-3.0T to obtain a sintered blank;

[0015] Preferably, the grinding step comprises: crushing the obtained sintered blank, grinding it into fine powder using an agate mortar, and then sieving it under a 200-mesh sieve to obtain alloy absorbing powder;

[0016] The present invention provides a magnetic wave absorbing material having excellent wave absorbing performance in the S band and a preparation method thereof, which has the following advantages over the prior art:

[0017] (1) The alloy magnetic absorbing material prepared in the present invention can have excellent microwave absorption effect and bandwidth between 2-4 GHz, effectively ensuring the performance of the material and improving the application range of the material;

[0018] (2) The preparation process of the alloy magnetic absorbing material of the present invention is simple, easy to operate, suitable for large-scale production, and not prone to waste.

[0019] Instruction manual attached:

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0021] Figure 1 This is a test result diagram of the alloy absorbing material of Example 1;

[0022] Figure 2 This is a graph showing the test results of the alloy absorbing material of Example 2;

[0023] Figure 3 This is a graph showing the test results of the alloy absorbing material of Example 3. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] Preparation of alloy magnetic absorbing materials:

[0027] 1. Using metals La, Fe, Ge, V, Mn, Zn, Sn with a purity greater than 99.0% as raw materials, according to LaFe 3.1 Ge 0.6 V 0.3 Mn 7.5 Zn 0.1 Sn 0.4 Atomic proportioning for batching;

[0028] 2. Melt in a standard vacuum melting furnace under argon protection and cast to obtain alloy ingots;

[0029] 3. The obtained alloy ingots were crushed into coarse powders with a particle size of less than 0.5 mm, and then sieved through a 40-mesh sieve to obtain alloy coarse powder; the crushed alloy coarse powder and zirconia balls were placed in a zirconia tank at a mass ratio of 15:1, and ball milled for 5 hours under the protection of anhydrous ethanol at a ball mill speed of 300 r / min;

[0030] 4. The ball-milled powder was taken out of a nitrogen-protected glove box, dried, and pressed into a blank with a diameter of 20 mm and a height of 10 mm;

[0031] 5. Place the blank into a vacuum magnetic field microwave sintering furnace for high-temperature sintering at a temperature of 1000°C for 20 minutes at a microwave frequency of 3.5kW and a magnetic field of 3.0T to obtain a sintered blank;

[0032] 6. The sintered blank was crushed, ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain alloy absorbing powder.

[0033] Embodiment 2:

[0034] Preparation of alloy magnetic absorbing materials:

[0035] 1. Using metals La, Fe, Ge, V, Mn, Zn, Sn with a purity greater than 99.0% as raw materials, according to LaFe 3.5 Ge 0.4 V 0.1 Mn 7.0 Zn 0.3 Sn 0.7 Atomic proportioning for batching;

[0036] 2. Melt in a standard vacuum melting furnace under argon protection and cast to obtain alloy ingots;

[0037] 3. The obtained alloy ingots were crushed into coarse powders with a particle size of less than 0.5 mm, and then sieved through a 40-mesh sieve to obtain alloy coarse powder; the crushed alloy coarse powder and zirconia balls were placed in a zirconia tank at a mass ratio of 15:1, and ball milled for 8 hours under the protection of anhydrous ethanol at a ball mill speed of 240 r / min;

[0038] 4. The ball-milled powder was taken out of a nitrogen-protected glove box, dried, and pressed into a blank with a diameter of 20 mm and a height of 10 mm;

[0039] 5. Place the blank into a vacuum magnetic field microwave sintering furnace for high-temperature sintering at 900°C for 30 minutes at a microwave frequency of 2.5kW and a magnetic field of 2.0T to obtain a sintered blank;

[0040] 6. The sintered blank was crushed, ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain alloy absorbing powder.

[0041] Embodiment 3:

[0042] Preparation of alloy magnetic absorbing materials:

[0043] 1. Using metals La, Fe, Ge, V, Mn, Zn, Sn with a purity greater than 99.0% as raw materials, according to LaFe 3.3 Ge 0.2 V 0.5 Mn 7.4 Zn 0.5 Sn 0.1 Atomic proportioning for batching;

[0044] 2. Melt in a standard vacuum melting furnace under argon protection and cast to obtain alloy ingots;

[0045] 3. The obtained alloy ingots were crushed into coarse powders with a particle size of less than 0.5 mm, and then sieved through a 40-mesh sieve to obtain alloy coarse powder; the crushed alloy coarse powder and zirconia balls were placed in a zirconia tank at a mass ratio of 15:1, and ball milled for 15 hours under the protection of anhydrous ethanol at a ball mill speed of 200 r / min;

[0046] 4. Take out the ball-milled powder from a nitrogen-protected glove box, dry it, and press it into a blank with a diameter of 20 mm and a height of 10 mm;

[0047] 5. Place the blank into a vacuum magnetic field microwave sintering furnace for high-temperature sintering at 800°C for 40 minutes at a microwave frequency of 1.0 kW and a magnetic field of 1.0 T to obtain a sintered blank;

[0048] 6. The sintered blank was crushed, ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain alloy absorbing powder.

[0049] Detection:

[0050] The alloy powder and paraffin of the above embodiment were mixed in a ratio of 82:18 (mass ratio) to prepare coaxial samples with inner and outer diameters of 3 mm and 7 mm, respectively, and thicknesses of 1.0 mm, 1.3 mm, 1.6 mm, 1.9 mm, 2.2 mm, and 2.5 mm, respectively. The coaxial samples were measured for complex permeability and complex dielectric constant in the 2-8 GHz frequency band using an HP8722ES microwave vector network analyzer. The reflectivity R of the single-layer absorbing material was simulated and calculated using the measured complex permeability and complex dielectric constant data according to the following formula.

[0051]

[0052] Medium r , μ rand d are the relative dielectric constant, relative magnetic permeability and thickness of the absorbing material, respectively, f is the frequency of the electromagnetic wave, C is the propagation speed of the electromagnetic wave in free space (i.e. the speed of light), and j is an imaginary unit.

[0053] Among them, LaFe in Example 1 3.1 Ge 0.6 V 0.3 Mn 7.5 Zn 0.1 Sn 0.4 Alloy absorbing powder test results are shown in Figure 1 ,from Figure 1 It can be seen that in all thicknesses, the minimum reflectivity peak is less than -20dB, and has a good broadband effect. When the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -19.7dB at 5.6GHz; when the composite thickness is 1.5mm, the minimum reflectivity peak reaches about -19.8dB at 4.6GHz; when the thickness is 2.0mm, the minimum reflectivity peak reaches about -20.0dB at 3.9GHz; when the composite thickness is 2.5mm, the minimum reflectivity peak reaches about -19.9 at 3.4GHz. When the thickness of the composite is 3.0 mm, its minimum reflectivity peak value reaches about -19.3 dB at 3.0 GHz; when the thickness of the composite is 3.5 mm, its minimum reflectivity peak value reaches about -18.7 dB at 2.7 GHz; when the thickness of the composite is between 1.0 and 3.5 mm, the minimum reflectivity of the composite falls between the S band (2-8 GHz), and it has excellent microwave absorption effect and bandwidth.

[0054] In Example 2, LaFe 3.5 Ge 0.4 V 0.1 Mn 7.0 Zn 0.3 Sn 0.7 The powder test results are shown in Figure 2 ,from Figure 2It can be seen that: in all thicknesses, the minimum reflectivity peak is less than -20dB, and has a good broadband effect. When the composite thickness is 1.0mm, the minimum reflectivity peak at 3.7GHz frequency reaches about -35.5dB; when the composite thickness is 1.5mm, the minimum reflectivity peak at 3.4GHz frequency reaches about -41.9dB; when the thickness is 2.0mm, the minimum reflectivity peak at 3.0GHz reaches about -32.2dB; when the composite thickness is 2.5mm When the thickness of the composite is 3.0mm, the minimum reflectivity peak value reaches about -34.2dB at 2.6GHz; when the thickness of the composite is 3.0mm, the minimum reflectivity peak value reaches about -28.6dB at 2.4GHz; when the thickness of the composite is 3.5mm, the minimum reflectivity peak value reaches about -28.5dB at 2.2GHz; when the thickness of the composite is 1.0-3.5mm, the minimum reflectivity of this composite falls between the frequency of 2-4GHz in the S band, and it has relatively excellent low-frequency microwave absorption effect and bandwidth.

[0055] In Example 3, LaFe 3.3 Ge 0.2 V 0.5 Mn 7.4 Zn 0.5 Sn 0.1 The powder test results are shown in Figure 3 ,from Figure 3 It can be seen that: in all thicknesses, the minimum reflectivity peak is less than -20dB, and has a good broadband effect. When the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -36.4dB at 4.6GHz; when the composite thickness is 1.5mm, the minimum reflectivity peak reaches about -34.4dB at 3.8GHz; when the thickness is 2.0mm, the minimum reflectivity peak reaches about -35.2dB at 3.2GHz; when the composite thickness is 2.5mm, the minimum reflectivity peak reaches about -36.4dB at 4.6GHz; when the composite thickness is 1.5mm, the minimum reflectivity peak reaches about -34.4dB at 3.8GHz; when the thickness is 2.0mm, the minimum reflectivity peak reaches about -35.2dB at 3.2GHz; when the composite thickness is 2.5mm, the minimum reflectivity peak reaches about -36.4dB at 4.6GHz; when the composite thickness is 1.5mm, the minimum reflectivity peak reaches about -36.4dB at 3.8GHz; when the composite thickness is 2 ... When the thickness of the composite is 3.0mm, the minimum reflectivity peak value reaches about -40.9dB at 2.8GHz; when the thickness of the composite is 3.0mm, the minimum reflectivity peak value reaches about -35.8dB at 2.5GHz; when the thickness of the composite is 3.5mm, the minimum reflectivity peak value reaches about -31.7dB at 2.2GHz; when the thickness of the composite is between 1.5-3.5mm, the minimum reflectivity of this composite falls between the frequency of 2-4GHz in the S band, and has relatively excellent low-frequency absorbing performance.

[0056] In summary, the materials prepared in the present invention have excellent wave absorbing performance in the S band.

[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0058] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A magnetic wave absorbing material having excellent wave absorbing performance in the S band, characterized in that: The magnetic wave absorbing material is a LaFe4Mn8 alloy magnetic wave absorbing material, and the composition of the alloy magnetic wave absorbing material according to the atomic ratio is LaFe 4-x- y Ge x V y Mn 8-Z-R Zn z Sn R ; The preparation method of the magnetic wave absorbing material comprises the following steps: (1) Ingredients: Select metals La, Fe, Ge, V, Mn, Zn, and Sn with a metal purity greater than 99.0% as raw materials, according to LaFe 4-x- y Ge x V y Mn 8-Z-R Zn z Sn R The ingredients are prepared according to the atomic ratio, and in the atomic ratio, 0.2≤x≤0.6; 0.1≤y≤0.5; 0.1≤z≤0.5; 0.1≤R≤0.7; (2) Melting: placing the metal materials after the above ingredients in a vacuum melting furnace for melting, and casting to obtain alloy ingots; (3) Ball milling: crushing the alloy ingot to prepare alloy coarse powder, and then ball milling the alloy coarse powder to obtain ball milled powder for later use; (4) Molding: The ball-milled powder is taken out of a nitrogen-protected glove box, dried, and then pressed into a blank; (5) Sintering: placing the blank into a vacuum magnetic field microwave sintering furnace for sintering to obtain a sintered blank for use; (6) Grinding: The sintered blank is crushed, ground and sieved to obtain alloy absorbing powder.

2. The magnetic wave absorbing material having excellent wave absorbing performance in the S band according to claim 1, characterized in that: The smelting in step (2) needs to be carried out under argon protection.

3. The magnetic wave absorbing material having excellent wave absorbing performance in the S band according to claim 1, characterized in that: In the step (3), the alloy coarse powder is sieved through a 40-mesh sieve, and during ball milling, the alloy coarse powder and zirconium oxide balls are placed in a zirconium oxide tank at a mass ratio of 15:1, and ball milled for 5-12 hours under the protection of anhydrous ethanol, wherein the speed of the ball mill is 200-300 r / min.

4. The magnetic wave absorbing material having excellent wave absorbing performance in the S band according to claim 1, characterized in that: In step (4), the diameter of the blank is 20 mm and the height is 10 mm.

5. The magnetic wave absorbing material having excellent wave absorbing performance in the S band according to claim 1, characterized in that: In the step (5), the sintering temperature is 800-1000° C., the holding time is 20-40 min, the microwave frequency is 1.0-3.5 kW, and the magnetic field is 1.0-3.0 T.

6. The magnetic wave absorbing material having excellent wave absorbing performance in the S band according to claim 1, characterized in that: In the step (6), the alloy absorbing powder needs to pass through a 200-mesh sieve.